Using Mathematics to Teach Accounting Principles - Sony Warsono (The Indonesian Journal of Accounting Research, 2015)
Abstract: As widely acknowledged, Luca Pacioli discussed accounting in his mathematics book Summa de Arithmetica, Geometria, Proportioni et Proportionalita. Using the perspective of mathematics, this paper shows that the majority of available accounting principles literature employs accounting equations positioning the elements of both assets and expenses in opposite accounting equations, rather than placing the two elements in the same side of the accounting equation. More than just offering consistent rationality, the use of mathematics rationality will make it much simpler to explain why the elements of assets and expenses should receive the same treatment concerning debits and credits. Furthermore, this paper shows that the rules of debits and credits are entirely based on mathematical logic. Finally, this paper proposes the need for learning to account from the perspective of mathematics, in addition to those of GAAP and engineering skills.Abstrak: Sebagaimana diakui secara luas, Luca Pacioli membahas akuntansi dalam buku matematikanya Summa de Arithmetica, Geometria, Proportioni et Proportionalita. Dengan menggunakan perspektif matematika, makalah ini menunjukkan bahwa sebagian besar prinsip akuntansi akuntansi yang tersedia menggunakan persamaan akuntansi yang memposisikan unsur-unsur dari kedua aset dan biaya dalam persamaan akuntansi yang berlawanan, daripada menempatkan dua elemen di sisi yang sama dari persamaan akuntansi. Lebih dari sekadar menawarkan rasionalitas yang konsisten, penggunaan rasionalitas matematika akan membuatnya lebih mudah untuk menjelaskan mengapa unsur-unsur aset dan pengeluaran harus menerima perlakuan yang sama mengenai debet dan kredit. Selanjutnya, tulisan ini menunjukkan bahwa aturan debit dan kredit sepenuhnya didasarkan pada logika matematika. Akhirnya, makalah ini mengusulkan perlunya belajar untuk memperhitungkan dari perspektif matematika, selain dari GAAP dan keterampilan teknik.